Pro SharePoint disaster recovery and high availability - Cummins, Stephen, 1971- (Expert's voice in SharePoint., 2013)
Focuses equally on disaster prevention and then disaster response, including coverage of cloud computing and cloud availability, an area untouched by other disaster recovery/high availability titles.